Aberrant Salience and Disorganized Symptoms as Mediators of Psychosis - Ceballos-Munuera, Celia; Senín-Calderón, Cristina; Fernández-León, Sandra; Fuentes-Márquez, Sandra; Rodríguez-Testal, Juan Fco. (Frontiers in Psychology, 2022)
Introduction: Ideas of reference (IR) are frequent in psychopathology, mainly in psychotic disorders. The frequency of IR and preoccupation about them are related to the psychotic dimension, and to a lesser extent, to negative or emotional disorganized dimensions. Aberrant salience (AS), has been proposed as an indicator of the onset of psychosis, particularly of schizophrenia. This study analyzed the mediating role of AS, disorganized symptoms and preoccupation about IR in the relationship between IR and the psychotic dimension. Method: The sample consisted of 330 participants (116 university students and 214 clinically active patients), 62.4% of whom were women aged 18 to 79. The REF IR scale, the Aberrant Salience Inventory (ASI) and the Brief Psychiatric Rating Scale (BPRS) were administered. Results: Evidence of a partial mediation model showed that the relationships between IR and the psychotic dimension were mediated jointly by AS and the disorganized dimension, and preoccupation about IR no longer had a role. This relationship was significantly influenced by participant age. The variables in the model explained 54.16% of the variance. Conclusions: The model proposed enabled a set of vulnerabilities (unusual thought content) to be predicted that could lead to a high-risk general pathological state and proneness to psychosis in particular. These findings are discussed with regard to early detection and prevention of psychosis.